An Epidemic Analogy Highlights the Importance of Targeted Community Engagement in Spaces Susceptible to Misinformation - Osman, Aya; Ogbunugafor, C. Brandon (Frontiers in Communication, 2022)
The study of the misinformation and disinformation epidemics includes the use of disease terminology as an analogy in some cases, and the formal application of epidemiological principles to describe or quantify how falsehoods are propagated in others. While these have been effective in reframing how to actively prevent the spread of misinformation, they have less to say about other, more indirect means through which misinformation can be addressed in marginalized communities. In this perspective, we develop a conceptual model based on an epidemiology analogy that offers a new lens on science-driven community engagement. Rather than simulate the particulars of a given misinformation outbreak, our framework instead suggests how activities might be engineered as interventions to fit the specific needs of marginalized audiences, towards undermining the invasion and spread of misinformation. We discuss several communication activities--in the context of the COVID-19 pandemic and others—and offer suggestions for how practices can be better orchestrated to fit certain contexts. We emphasize the utility of our model for engaging communities distrustful of scientific institutions.